Mini-Suomi -terveystutkimuksen toteutus = The execution of the Mini-Finland health survey. Osa = Part 2, Verenkiertoelinten ja hengityselinten sairauksien tutkimusmenetelmät = Cardiovascular and respiratory survey methods - Aromaa, Arpo (Kansaneläkelaitoksen julkaisuja, ISSN 0355-483X, 1985)
English summary.
Keywords: Respiratory Tract Diseases; Health Surveys; Data Collection; Cardiovascular Diseases : diagnosis; Cardiovascular Diseases; Health Surveys : Finland; Respiratory Tract Diseases : diagnosis; terveystutkimus; terveydenhuolto; sydäntaudit; sydän- ja verisuonitaudit; tutkimusmenetelmät; hengityselinten taudit; kansanterveys; keuhkosairaudet; hälsoforskning; hälso- och sjukvård; hjärtsjukdomar; hjärt-kärlsjukdomar; forskningsmetoder; andningsorganens sjukdomar; folkhälsa; lungsjukdomar